2022
DOI: 10.3390/ijerph191911874
|View full text |Cite
|
Sign up to set email alerts
|

GO-TiO2 as a Highly Performant Photocatalyst Maximized by Proper Parameters Selection

Abstract: The synthesis and characterization of novel graphene oxide coupled to TiO2 (GO-TiO2) was carried out in order to better understand the performance of this photocatalyst, when compared to well-known TiO2 (P25) from Degussa. Thus, its physical-chemical characterization (FTIR, XRD, N2 isotherms and electrochemical measurements) describes high porosity, suitable charge and high electron mobility, which enhance pollutant degradation. In addition, the importance of the reactor set up was highlighted, testing the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The addition of H 2 O 2 to the photocatalytic process (UV/TiO 2 ) can help enhance the TMP degradation efficiency because the UV/H 2 O 2 process can cause the release of a large number of OH• radicals to participate in the oxidation reactions of pollutant compounds 10 . Furthermore, H 2 O 2 is an oxidant that can also contribute to the activation of TiO 2 catalysts by removing contaminants from their surfaces 24 . Figure 4 shows that, when adding H 2 O 2 to the TiO 2 suspension, hydrogen peroxide quickly adsorbs to the TiO 2 catalyst surface to form Ti‐OOH complexes 25 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of H 2 O 2 to the photocatalytic process (UV/TiO 2 ) can help enhance the TMP degradation efficiency because the UV/H 2 O 2 process can cause the release of a large number of OH• radicals to participate in the oxidation reactions of pollutant compounds 10 . Furthermore, H 2 O 2 is an oxidant that can also contribute to the activation of TiO 2 catalysts by removing contaminants from their surfaces 24 . Figure 4 shows that, when adding H 2 O 2 to the TiO 2 suspension, hydrogen peroxide quickly adsorbs to the TiO 2 catalyst surface to form Ti‐OOH complexes 25 .…”
Section: Resultsmentioning
confidence: 99%
“…10 Furthermore, H 2 O 2 is an oxidant that can also contribute to the activation of TiO 2 catalysts by removing contaminants from their surfaces. 24 Figure 4 shows that, when adding H 2 O 2 to the TiO 2 suspension, hydrogen peroxide quickly adsorbs to the TiO 2 catalyst surface to form Ti-OOH complexes. 25 So, H 2 O 2 can act as an electron trap to limit e -/h + recombination.…”
mentioning
confidence: 99%
“…Photocatalytic oxidation takes advantage of the strong oxidation capacity of the photocatalyst oxidant to open the ring and remove nitrogen, before finally realizing complete mineralization, making it lose toxicity without secondary pollution. Among them, TiO 2 has become a research hotspot of photocatalysts due to its high chemical stability, non-toxic, low cost and other advantages, and its photostability and efficiency are highly favored [ 13 , 14 , 15 , 16 , 17 ]. Ortega Liébana et al found that 3-chloropyridine was completely mineralized under TiO 2 photocatalysis [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…With WLP (without H 2 O 2 ), it was possible to remove more than 73% of the PAHs tested from the outer layer of PFPC in 3 days. Díez et al [18] carried out the synthesis and characterization of novel graphene oxide coupled to TiO 2 (GO-TiO 2 ) in order to better understand the performance of this photocatalyst compared to the well-known TiO 2 (P25) from Degussa. Checa et al [19] synthesized and characterized a magnetic graphene oxide titania (FeGOTi) catalyst for application in primidone removal from water, and checked for any possible enhancements.…”
mentioning
confidence: 99%